Long‐term clinical and functional outcome following treatment for Paget–Schroetter syndrome. Issue 11 (4th September 2013) - Taylor, J. M.; Telford, R. J.; Kinsella, D. C.; Watkinson, A. F.; Thompson, J. F.
<x xml:space="preserve">Abstract</x> Background Effort‐related thrombosis of the axillosubclavian vein (Paget–Schroetter syndrome, PSS) is uncommon. It tends to affect young, active individuals and yet consensus on management is lacking. The aim here was to analyse late outcomes in a series of patients treated for PSS using a standard protocol. Methods The medical records of patients treated for PSS over 16 years were analysed. Patients were divided into four groups according to their management. Clinical and functional outcomes were analysed regarding residual venous defects after treatment, and Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire scores, respectively. Results Some 117 patients (52 men and 65 women, mean age 32 years) were included. Catheter‐directed thrombolysis was successful in 42 of 56 treated patients. Thoracic outlet decompression surgery was performed in 95 patients. DASH scores improved significantly in patients treated surgically (P < 0.001 to P = 0·009); early surgery had a better outcome than delayed surgery (P = 0·040). Patients who were managed conservatively showed no improvement (P = 0·116). Where venoplasty was necessary, it was successful in 18 of 25 patients. A short duration of lysis (less than 24 h) increased the risk of rethrombosis (P = 0·020). The method of postoperative anticoagulation had no influence on the rate of rethrombosis. Conclusion Patients treated surgically for PSS had better functional outcomes than those managed conservatively. Prompt thrombolysis and surgery was superior to delayed management with respect to rethrombosis and functional outcome.